2021
DOI: 10.7554/elife.59295
|View full text |Cite
|
Sign up to set email alerts
|

4-Hydroxy-2-nonenal antimicrobial toxicity is neutralized by an intracellular pathogen

Abstract: Pathogens encounter numerous antimicrobial responses during infection, including the reactive oxygen species (ROS) burst. ROS-mediated oxidation of host membrane poly-unsaturated fatty acids (PUFAs) generates the toxic alpha-beta carbonyl 4-hydroxy-2-nonenal (4-HNE). Though studied extensively in the context of sterile inflammation, research into 4-HNE's role during infection remains limited. Here we found that 4-HNE is generated during bacterial infection, that it impacts growth and survival in a range of bac… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Because this phenotype is rescued by constitutive activation of PrfA, a bacterial transcription factor activated upon entry into host cell cytosol, the authors speculate that host-derived MG is a cue that bacteria sense to activate transcription of virulence genes. In addition, Woodward and co-workers [ 45 ] proposed L. monocytogenes encodes genes to deal with 4-HNE generated by ROS during infections. In this study, the authors looked for genes that were induced in the presence of 4-HNE, with the hypothesis that these genes encode detoxifying products of this lipid aldehyde encountered in animal tissues.…”
Section: Aldehydes Beyond Mycobacterium Tuberculosis ...mentioning
confidence: 99%
“…Because this phenotype is rescued by constitutive activation of PrfA, a bacterial transcription factor activated upon entry into host cell cytosol, the authors speculate that host-derived MG is a cue that bacteria sense to activate transcription of virulence genes. In addition, Woodward and co-workers [ 45 ] proposed L. monocytogenes encodes genes to deal with 4-HNE generated by ROS during infections. In this study, the authors looked for genes that were induced in the presence of 4-HNE, with the hypothesis that these genes encode detoxifying products of this lipid aldehyde encountered in animal tissues.…”
Section: Aldehydes Beyond Mycobacterium Tuberculosis ...mentioning
confidence: 99%
“…S3). A fourth α,β-unsaturated aldehyde that was tested is 4-HNE, which is a degradation product of polyunsaturated fatty acids that is formed during the oxidative burst as part of the cellular immunity ( 34 , 35 ). Since the compound is bactericidal at low concentrations and may play a role in pathogen elimination during infection, we tested its activity in a killing assay rather than in a growth inhibition assay ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The α,β-unsaturated aldehyde group of 4-HNE easily undergoes a Michael-type addition reaction with thiol and amino groups of proteins to generate protein adducts, and this reactivity is held responsible for its antibacterial activity ( 34 , 37 , 38 ). A recent study found that two NADPH-dependent oxidoreductases, namely, the flavin-dependent enone reductase Rha1 and the alcohol/quinone reductase Rha2, play pivotal roles in the resistance of L. monocytogenes against 4-HNE ( 35 ). Recombinant Rha1 and Rha2 reduced the C=C double bond of 4-HNE, generating 4-hydroxynonanal in a NADPH-dependent manner.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations